2020
DOI: 10.3892/or.2020.7727
|View full text |Cite
|
Sign up to set email alerts
|

N‑glycosylation and receptor tyrosine kinase signaling affect claudin‑3 levels in colorectal cancer cells

Abstract: Changes in protein levels in different components of the apical junctional complex occur in colorectal cancer (CRC). Claudin-3 is one of the main constituents of tight junctions, and its overexpression can increase the paracellular flux of macromolecules, as well as the malignant potential of CRC cells. The aim of this study was to investigate the molecular mechanisms involved in the regulation of claudin-3 and its prognostic value in CRC. In silico evaluation in each of the CRC consensus molecular subtypes (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Studies demonstrated that overexpression of claudin‐3 can increase the paracellular flux of macromolecules and the malignant potential of CRC cells. They concluded that the expression of CLDN3 can be used to predict the prognosis of CRC 26–28 . Von Willebrand factor (VWF) and MUC2 are believed to have shared a common ancestor 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that overexpression of claudin‐3 can increase the paracellular flux of macromolecules and the malignant potential of CRC cells. They concluded that the expression of CLDN3 can be used to predict the prognosis of CRC 26–28 . Von Willebrand factor (VWF) and MUC2 are believed to have shared a common ancestor 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Many claudins are dysregulated in a range of cancers, as in the case of the CLDN1 and CLDN2 genes, which are overexpressed in colorectal cancer ( Dhawan et al, 2011 ; Mori et al, 2011 ; Pope et al, 2014 ; Wang et al, 2019 ). CLDN3 is similarly overexpressed at the mRNA level in CRC tumors that belong to the consensus molecular subgroup (CMS)-CMS2 and CMS3, which correspond to a poor prognosis ( Tang et al, 2011 ; Perez et al, 2020 ). Colorectal cancers have significant levels of CLDN4 expression ( Georges et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced expression indicates an increase in the malignant potential. However, the authors note that this effect depends on the molecular subtype of colorectal cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%